The deadly coronaviruses: The 2003 SARS pandemic and the 2020 novel coronavirus epidemic in China. Issue 109 (May 2020) - Yang, Yongshi; Peng, Fujun; Wang, Runsheng; Guan, Kai; Jiang, Taijiao; Xu, Guogang; Sun, Jinlyu; Chang, Christopher
Abstract: The 2019-nCoV is officially called SARS-CoV-2 and the disease is named COVID-19. This viral epidemic in China has led to the deaths of over 1800 people, mostly elderly or those with an underlying chronic disease or immunosuppressed state. This is the third serious Coronavirus outbreak in less than 20 years, following SARS in 2002–2003 and MERS in 2012. While human strains of Coronavirus are associated with about 15% of cases of the common cold, the SARS-CoV-2 may present with varying degrees of severity, from flu-like symptoms to death. It is currently believed that this deadly Coronavirus strain originated from wild animals at the Huanan market in Wuhan, a city in Hubei province. Bats, snakes and pangolins have been cited as potential carriers based on the sequence homology of CoV isolated from these animals and the viral nucleic acids of the virus isolated from SARS-CoV-2 infected patients. Extreme quarantine measures, including sealing off large cities, closing borders and confining people to their homes, were instituted in January 2020 to prevent spread of the virus, but by that time much of the damage had been done, as human-human transmission became evident. While these quarantine measures are necessary and have prevented a historical disaster along the lines of the Spanish flu, earlier recognition and earlier implementation of quarantine measures may have been even more effective. Lessons learned from SARS resulted in faster determination of the nucleic acid sequence and a more robust quarantine strategy. However, it is clear that finding an effective antiviral and developing a vaccine are still significant challenges. The costs of the epidemic are not limited to medical aspects, as the virus has led to significant sociological, psychological and economic effects globally. Unfortunately, emergence of SARS-CoV-2 has led to numerous reports of Asians being subjected to racist behavior and hate crimes across the world. Highlights: The 2019-nCoV is officially called SARS-CoV-2, and is the cause of the disease named COVID-19. COVID-19 is the third severe epidemic caused by coronaviruses in the past 20 years. It is believed that the SARS-CoV-2 virus originated from bats, based on genomic sequencing. While human strains of Coronavirus are associated with about 15% of cases of the common cold, the SARS-CoV-2 is far more deadly, with a mortality rate around 2.3%. As of February 19th, 2020, there have been 75, 282 confirmed cases and 2012 deaths worldwide. Lessons learned from SARS in 2003 resulted in faster determination of the nucleic acid sequence and a more robust quarantine strategy. Extreme quarantine measures, including sealing off large cities, closing borders and confining people to their homes are critical to stemming spread of the virus. Pyroptosis, a novel form of inflammatory cell death, is a possible mechanism for the increased virulence of the SARS-CoV-2.